Medição da energia cinética das chuvas e definição de um índice pluvial para estimativa da erosividade em Arvorezinha/RS - Ramon, Rafael (2017)
One of the challenges of modern agriculture is adapting to climatic effects, including the capability of rainfall events in causing erosion. Understanding the climatic phenomena depends on the monitoring of rain variables that express the magnitude and pattern of erosive agents. The kinetic energy of rain (E) and the maximum intensity of 30 minutes (I30) are key variables to represent the capability of rain in causing erosion, and the product of the two being one of the most known and used erosivity indices (EI30). However, in Brazil, to obtain direct and continuous measurements of E are incipient, as long series of rain intensity data (I) are scarce. Therefore, empirical equations based on rainfall information that are easy to acquire as daily or monthly accumulated rain (P) are used. The aim of this study is to analyze a set of data with hydrological variables, especially rainfall characteristics (volume, duration and energy) responsible for triggering the erosion process and its relationship with flow behavior (Q), suspended sediment concentration (SSC) and sediment yield (SY) in a rural catchment. From the analysis of the variables, E and EI30 estimation equations are proposed for the study site. The study was conducted in a 1.23 km² experimental catchment located in southern Brazil, where monitoring of the main hydrological flows (P, Q and SSC) has been carried out since 2002. P is monitored with pluviometers and rain gauges, and E has been measured since 2014 by a disdrometer (Parsivel2 - OTT). From this set of data, different equations for the estimation of E=f(I) and models for the estimation of EI30 were explored. Complementarily, a comparison was made between the equations obtained with equations available in the literature for the estimation of E and EI30. Additionally, this study also explored seasonal variations in rainfall characteristics (I30 P, E) and related them to Q, SSC and SY of the catchment in order to demonstrate the importance of E and I30 for the hydrossedimentological modeling. The measured E values were similar to the values estimated by the equations of Foster et al. (1981) and van Dijk et al. (2002), while Brown and Foster (1987) equation underestimate the values of E. EI30 was also quantified over a period of 8 years and an equation was proposed to estimate EI30 by accumulated daily rainfall variables. From 15 years of data, an annual EI30 value is presented and its average distribution between the 12 months of the year. The main results are: (a) a new equation for estimating E from the I measurement, its seasonal variability and similarities with equations previously known; (B) the relationship between measured E data and measured hydrological variables at catchment scale; (C) the EI30 factor for the Arvorezinha/RS region; (D) new indices for estimating EI30 from daily rainfall records.